Recent Literature on British Unemployment Insurance - Tolles, Newman Arnold (Quarterly Journal of Economics, 1925)
Recent Literature on British Unemployment Insurance Get access Newman Arnold Tolles Newman Arnold Tolles Hakvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 39, Issue 4, August 1925, Pages 651–662, https://doi.org/10.2307/1883271 Published: 01 August 1925